Effect of employee's needs and organizational design on perception of TQM effectiveness (2002)
The paper assesses the effect of two psychological variables (employees needs and organizational design) on employees' perception of TQM effectiveness. A total of 80 respondents drawn from two organizations in Lagos practicing TMQ participated in the study. Data were collected by means of questionnaires. Four hypotheses were tested and confirmed by the results from findings. Employees' needs and organizational design showed significant impact (at P<0.01) on employee's perception of the effectiveness of TQM practices in the sampled organizations. Growth need had the most significant effect on the perception of TQM effectiveness in the study